2008
DOI: 10.1002/cphc.200800068
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Interactions between Stable Piperidine‐1‐yloxyl Derivatives and an Ionic Liquid

Abstract: 2,2,6,6-Tetramethylpiperidine-1-yloxyl derivatives substituted with either hydrogen bonding [-OH, -OSO(3)H] or ionic [-OSO(3) (-)Na(+), -OSO(3) (-)K(+), N(+)(CH(3))(3)I(-), N(+)(CH(3))(3) N(-)(SO(2)-CF(3))(2)] substituents are investigated in 1-butyl-3-methylimidazolium tetrafluoroborate over a wide temperature range covering both glassy and viscous states. The Vogel-Fulcher-Tammann equation describes the temperature dependence of the ionic liquid viscosity. Quantum chemical calculations of the spin probes at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 70 publications
0
33
0
Order By: Relevance
“…The mobility of stable nitroxide radical provides information on local viscosity and environment, and this approach is widely used in various fields of science, including 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 studies of ILs. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] However, in most cases previous CW EPR data were obtained at temperatures close to ambient and well above melting temperatures of corresponding ILs, and only a few works addressed the low temperature regions between glass transition (T g ) and melting (T m ) temperatures.…”
Section: Auxiliary Cw Epr Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mobility of stable nitroxide radical provides information on local viscosity and environment, and this approach is widely used in various fields of science, including 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 studies of ILs. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] However, in most cases previous CW EPR data were obtained at temperatures close to ambient and well above melting temperatures of corresponding ILs, and only a few works addressed the low temperature regions between glass transition (T g ) and melting (T m ) temperatures.…”
Section: Auxiliary Cw Epr Studiesmentioning
confidence: 99%
“…A number of EPR studies in ILs using spin probes have been accomplished, both in neat ILs and in IL/water mixtures. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] In particular, it was shown that nanostructuring of ILs in water can be monitored via polaritydependent hyperfine splitting. However, in general, the shape of the nitroxide spectrum was found to be not very sensitive to the effects of nanostructuring, therefore developing other types of probes for heterogeneities in ILs would be a topical task.…”
Section: Introductionmentioning
confidence: 99%
“…Stable radicals, so called spin probes, have been successfully used as model compounds to describe the mobility of reactive species in the ionic liquids. [8][9][10][11][12][13][14][15][16][17][18][19][20] Furthermore, the isotropic hyperfine coupling constants of the stable radicals give information about micropolarity of the surrounding matrix. 13,16,20-22 2,2,6,6-Tetramethylpiperidine-1-yloxyl derivatives are examples for spin probes, which have been successfully applied for the investigation of ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the ionic substituent at the 4 position with respect to the nitroxyl group significantly reduces the mobility of these spin probes in the ionic liquids caused by the additional ionic interactions between the ionic substituent and the individual ions of the ionic liquids. 13,14,16,20 Recently, a pyrrolidine-1-yloxyl derivative covalently bound via a spacer group to the imidazolium ion was described in the literature as further new spin probe for the investigation of ionic liquids. 21 In this Letter, we describe the synthesis of a 2,2,6,6-tetramethylpiperidine-1-yloxyl derivative that is covalently bound to the imidazolium ion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation